Determination of lipidomic differences between human breast cancer and surrounding normal tissues using HILIC-HPLC/ESI-MS and multivariate data analysis - Cífková, Eva; Holčapek, Michal; Lísa, Miroslav; Vrána, David; Gatěk, Jiří; Melichar, Bohuslav (Analytical and bioanalytical chemistry, 2015)
The comprehensive approach for the lipidomic characterization of human breast cancer and surrounding normal tissues is based on hydrophilic interaction liquid chromatography (HILIC)-electrospray ionization mass spectrometry (ESI-MS) quantitation of polar lipid classes of total lipid extracts followed by multivariate data analysis using unsupervised principal component analysis (PCA) and supervised orthogonal partial least square (OPLS). This analytical methodology is applied for the detailed lipidomic characterization of ten patients with the goal to find the statistically relevant differences between tumor and normal tissues. This strategy is selected for better visualization of differences, because the breast cancer tissue is compared with the surrounding healthy tissue of the same patient, therefore changes in the lipidome are caused predominantly by the tumor growth. A large increase of total concentrations for several lipid classes is observed, including phosphatidylinositols, phosphatidylethanolamines, phosphatidylcholines, and lysophosphatidylcholines. Concentrations of individual lipid species inside the abovementioned classes are also changed, and in some cases, these differences are statistically significant. PCA and OPLS analyses enable a clear differentiation of tumor and normal tissues based on changes of their lipidome. A notable decrease of relative abundances of ether and vinylether (plasmalogen) lipid species is detected for phosphatidylethanolamines, but no difference is apparent for phosphatidylcholines.
Keywords: nádory prsu; Female; Hydrophobic and Hydrophilic Interactions; multivariační analýza; ženské pohlaví; Multivariate Analysis; lipidy; lidé; fosfolipidy; fosfatidylcholiny; Chromatography, Liquid; Breast Neoplasms; Lipids; referenční hodnoty; Phosphatidylcholines; hmotnostní spektrometrie s elektrosprejovou ionizací; fosfatidylinositoly; Reference Values; fosfatidylethanolaminy; Phospholipids; Principal Component Analysis; Lysophosphatidylcholines; Phosphatidylethanolamines; analýza hlavních komponent; Phosphatidylinositols; lysofosfatidylcholiny; Spectrometry, Mass, Electrospray Ionization; chromatografie kapalinová; hydrofobní a hydrofilní interakce; Humans